Design of High Performance Decoder with Mixed Logic Styles - Khadir, Mohammad; Renukarani, S; Usharani, Tunikipati; Hemanth Kumar, D (International Journal of Engineering and Technology, 2018)
The CMOS technology is the mostly portable technology used in the designing of the circuits and in its fabrication. Designing of the circuits using CMOS technology requires the high power, high transistors count and low performance. The basic idea of the project is in order to reduce the count of transistors, time delay, and power consumption and to increase the performance of the circuits such as line decoders. The line decoder is a combinational circuits to which â€žnâ€Ÿ no .of inputs are given as input and the output is 2^n based on the selected input and it requires 20 and more than 20 transistors to design any MxN decoders using CMOS technology .In order to configure the parameters and to make it more portable we are using different types of logic styles this usage of technologies more than one technologies on each circuit is a mixed logic styles .In this concept we observe the results as per required .The technologies we use in this is TGL/DVL. The suggested framework â€œDesign about low Power, helter execution 2-4 What's more 4-16 blended rationale offering Decodersâ€ is executed done 45nm engineering utilizing cadence virtuoso tool. The circuit schematic is designed and the circuits are simulated for functionality verification.Â Â